Analisis Repurchase Intention pada Produk Local Brand Erigo berdasarkan Theory of Planned Behavior dan Customer Value dengan Customer Satisfaction sebagai Variabel Intervening - Wulandari, Destri; Fadhilah, Muinah; Welsa, Henny (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the influence of Subjective Norms (X1) and Customer Value (X2) on Repurchase Intention (Y) through Customer Satisfaction (Z) as an intervening variable among Erigo brand customers on Shopee. This type of research is quantitative, using Judgment Sampling or purposive sampling for sampling techniques, and data collection is conducted through surveys using questionnaires. The results show that subjective norms have a significant role in influencing repurchase intention. Customer value positively influences repurchase intention. Subjective norms positively affect customer satisfaction. Customer value has a positive impact on customer satisfaction. Customer satisfaction positively affects repurchase intention. In conclusion, customer satisfaction is able to mediate the variables of customer value and subjective norms with repurchase intention for the Erigo brand on Shopee. Keywords: Subjectiver norms, Customer Value, Repurchase Intention, Customer Satisfactio